THE INFLUENCE OF THE NAVIGATING NURSE BEFORE THE DIAGNOSIS AND START OF TREATMENT OF PATIENTS AFFECTED BY BREAST CANCER IN THE CITY OF GOIANIA (GO), BRAZIL - Queiroz, Bruna Gonçalves; Freitas-Junior, Ruffo (Mastology, 2021)
Objective: To evaluate and measure the time reduction in days between diagnosis and the start of treatment in patients guided by the navigating nurse or in patients attending outpatient clinics in a cancer referring Hospital. Methodology: This is a retrospective, analytical cohort study. The study was carried out in a specialized cancer hospital located in the city of Goiânia, GO. Data collection was performed at the Gynecology and Breast Service (SGM), using the data available in the medical records of women who were seen for the first time during the period from August 2018 to July 2019. Patients who met the eligibility criteria were classified into two groups (i.e., navigated and un-navigated). The data were analyzed using the SPSS version 23 statistical package, adopting a significance level of 5% (p<0.05), and the nonparametric test (Mann– Whitney U-test). Results: In total, 59 patients were included in the study. The patients aged 40–59 years (50.8%). There was a significant reduction in the mean delay in the group of patients guided by the navigating nurse: between the first consultation until the procedure (biopsy) for the diagnosis of breast cancer performed from 82.97 (SD 131.99) to 19.05 (SD 32.84) days, p=0.023; from the first consultation to the biopsy result from 105.41 (SD 137.94) to 30.95 (SD 36.92) days, p=0.002; and from the procedure to the biopsy result from 22.43 (SD 17.42) to 11.91 (SD 10.09) days, p=0.002. Conclusion: The performance of the navigator nurse provided an important reduction in different time intervals, allowing greater agility in the assistance and management of women with breast cancer, in a cancer referral hospital.